The Effect of Islamic Work Ethics toward Employee Performance - Noor Aflah, Kuntarno; Suharnomo, Suharnomo; mas'ud, Fuad (IQTISHADIA, 2021)
This study aims to analyze the factors which affect employee performance; islamic work ethics by using affective commitment and job satisfaction as intervening variables. Based on the research problem, there are how to improve employee performance through affective commitment and job satisfaction, and the factors which affective commitment and job satisfaction, so the answer is by the Islamic Work Ethics variable. This study is conducted on 200 employees of cross sectors and cross professions working in various fields. Data is processed using Structural Equation Modelling (SEM) by the help Analysis of Moment Structure (AMOS) program. The results show that Islamic Work Ethics has a positive effect on employee performance, by using affective commitment and job satisfaction as intervening variable